Enhance quality improvement through lean six sigma in division Side Board Clavinova Piano’s - Hernadewita Hernadewita; Indra Setiawan; Hendra Hendra (International Journal of Production Management and Engineering, 2022)
A lean production system is one of the main factors that every company must have to improve quality, especially reducing waste that occurs in the production line. The musical instrument industry such as Piano manufacturing includes industries that reduce waste by improving the manufacturing system. The company’s strategy to eliminate this waste is to create an effective and efficient work system. The piano production process still has several problems, such as the presence of waste. This is an obstacle in improving the quality of production by reducing the waste that occurs. For this reason, this research focuses on improving the quality of production by reducing waste that occurs, finding the cause of the problem and taking corrective action. The method used in this research is the integration of Lean and Six Sigma and the DMAIC framework. The process is waste flow and production problems are identified in Define phase and residual measurement is measured in Measurement phase. Fishbone diagrams and the application of FMEA are used to analyze the factors that cause problems that occur and prioritize improvements to solve these problems. The implementation of Value Stream Mapping (VSM) is applied to the Enhance of quality improvement phase to reduce waste. The results showed that product quality increased from an average sigma level of 3.53 to 3.79 where overproduction decreased by 41% and Side Board production leadtime decreased by 373 second.